Agriculture: sustainable crop and animal production to help mitigate nitrous oxide emissions - Snyder, CS; Davidson, EA; Smith, P; Venterea, RT (Current opinion in environmental sustainability, 2014)
•Selecting the right source, rate, time and place of N application is important.•New technologies and greater farmer/adviser skills can improve N input management.•Crop recovery of N may be increased >20%, reducing risks of N2O emissions >20–30%.•N use efficiency (NUE) is economically important to farmers, but N2O loss is not.•More cross-disciplinary research/outreach may improve farm NUE and N2O mitigation. Nitrous oxide (N2O) emissions from agriculture can be tackled by reducing demand for, and consumption of, nitrogen (N) inputs via diet modification and waste reduction, and/or through technologies applied at the field level. Here we focus on the latter options. Opportunities for mitigating N2O emissions at the field level can be advanced by a clearer scientific understanding of the system complexities leading to emissions, while maintaining agricultural system sustainability and productivity. A range of technologies are available to reduce emissions, but rather than focus specifically on emissions, the broader management and policy focus should be on improved N use efficiency and effectiveness; for lower N2O emissions per unit of crop and animal product, or per unit of land area.